Minor hallucinations in isolated rapid eye movement sleep behavior disorder indicative of early phenoconversion: A preliminary study. (23rd November 2021) - Sumi, Yukiyoshi; Ubara, Ayaka; Ozeki, Yuji; Kadotani, Hiroshi
Abstract : Objectives: Minor hallucinations (MH) are psychotic symptoms that can occur anywhere between prodromal to early Parkinson's disease and after onset of motor problems. MH include visual illusions, presence hallucinations, and passage hallucinations. Isolated rapid eye movement sleep behavior disorder (RBD) is a harbinger of neurodegenerative diseases. We conducted a retrospective cohort study to investigate the clinical characteristics of isolated RBD with MH and the risk of phenoconversion. Materials and methods: We retrospectively analyzed the data of 36 patients with isolated RBD (four females; median age, 75.0 years). We defined cases reporting at least one minor hallucination as RBD with MH. Demographic data and cognitive function were compared between patients with and without MH, and Cox proportional hazards models estimated the risk of phenoconversion. Results: We included 10 (27.8%) patients with MH and 26 (72.2%) without MH. Patients with MH were older, had less dopamine transporter accumulation, more severe autonomic dysfunction, more depressive symptoms, and lower verbal fluency and symbol coding test scores than patients without MH. After follow‐up (median, 2.50 years), 13.9% (5/36) of all patients developed phenoconversion (Parkinson's disease, two patients; dementia with Lewy bodies, three patients). The rate of phenoconversion was significantly higher in patients with MH (40.0% vs. 3.8%, p  = .005). The Cox proportional hazards model adjusted for age, sex, and disease duration revealed that MH was a significant risk factor for phenoconversion (hazard ratio, 14.72; 95% confidence interval, 1.35–160.5). Conclusions: Minor hallucinations may be utilized as early clinical markers for prodromal estimation of neurodegenerative diseases.